Eksplorasi Etnobotani Mesi Koro Gami sebagai Warisan Kuliner Lokal Suku Lio di Desa Wolotopo Kabupaten Ende - Daud, Maimunah H.; Mina, Estevania Inggrita; Ego, Agnesia Aprilia; Navi, Lusia Herlina; Mbere, Olivia Aprianti (Biocaster : Jurnal Kajian Biologi, 2025)
Mesi Koro Gami is a traditional food of the Lio people in Flores, East Nusa Tenggara, made from grated coconut roasted until dry and brown. This study aims to explore the process of making Mesi Koro Gami and the cultural values inherent in this food in the lives of the Lio people. The method used was descriptive qualitative, with data collection through interviews and direct field observations. The results show that Mesi Koro Gami has a distinctive savory taste and fragrant aroma, and is often consumed as a snack or mixed with staple foods such as sweet potatoes and corn. Besides being a daily food, Mesi Koro Gami also reflects a strong cultural heritage, demonstrating the close relationship between culinary practices and local community identity.